Pengaruh Jumlah Sudu Terhadap Kinerja Turbin Savonius - Jamal, Jamal (Politeknik Negeri Ujung Pandang, 2019)
Savonius wind turbines are wind turbines that canoperate at low wind speeds, this type of turbine is very suitable tobe used in several places in Indonesia. The research aims toimprove the performance of the Savonius wind turbine withvariations in the number of turbine blades as well as variations inthe velocity of wind speed. The research method wasexperimental where wind turbine testing was carried out withvariations in the number of turbine blades with number of 2, 3and 4 blades, other variations carried out were wind speed at 3.5;4,5; 5.5 and 6.5 m/s. The study results show that the 2-bladeturbine produces greater rotation, but the torque moment islower than the 3 and 4 blade turbines, this can be seen in the lowefficiency of the 2 blade turbine at low wind speeds with highloading. At 3.5 m / s wind turbines 2 blade turbines haveefficiency that tends to be the same as 3 and 4 blade turbines upto 0.5 N but at loads of 0.6 - 1.2 N 2 blade turbines have lowerefficiency, while at wind speeds of 4.5 - 6.5 m / s 2 blade turbineshave greater efficiency than turbines 3 and 4 blades up to a loadof 1.2 N but if the load is added then the efficiency of 2-bladeturbines can be smaller than efficiency 3 and 4-blade.